Effects of temperature and nutrition stress on Anopheles stephensi, an Indian urban malaria vector - Chaitali Ghosh; Naveen Kumar; Soumya Mogaveerthi; Sanjay Lamba; Chethan Kumar Ramanjini; Soumya Gopal Joshi; Priyanka Chandran; Sampath Kumar; Sunita Swain (Malaria Journal)
Abstract Background Changing climate and complexity in ecological landscape can potentially expand the geographic distribution of mosquitoes (Diptera: Culicidae) to adapt and transmit various vector-borne diseases, including malaria. Anopheles stephensi is a potential urban malaria vector in the Indian subcontinent. Temperature and nutrients are the important environmental stressors, which influence the life cycle and vectorial competence of mosquitoes. Methods Three experimental setups were designed in the laboratory by exposing An. stephensi to low-temperature (LT) at 4 °C for eggs and 18 ± 1 °C for larvae to adults, high-temperature (HT) at 35.5 ± 1 °C for all life stages, and low nutrition (NT) at 33 mg/100 larvae. Baseline assays were conducted before each experiment. Stress was induced to eggs, larvae, pupae and adults for 8 consecutive generations, whereas vectorial competence and chromosomal inversion experiments were performed on adult females at the 8th generation. Parameters of life-history traits, including fecundity (number of eggs), egg hatchability (fertility), developmental time, longevity of adults, sex ratio, egg and wing morphometrics, and pupal mass were measured for fitness status. The LT, HT and NT lines were infected with in vitro cultured Plasmodium falciparum parasites to compare the vectorial competence. Ovarian polytene chromosomes of the three stressed lines were analysed to check the structural differences on the chromosomal arms for adaptation due to stress conditions. The predictive mathematical modelling using linear regression was analysed to estimate the number of generations required for the stressed lines to become normal comparable to the control lines. Results Fecundity, egg hatchability, egg-to-adult developmental time, longevity of adults, egg and wing morphometrics, and pupal mass were decreased in HT and NT lines, whereas these parameters were increased in the LT line. The mosquitoes of HT and NT lines developed faster from egg to adult emergence (~ 7.5 and 11 days, respectively), whereas the duration was longer (~ 25 days) in the LT line. The oocyst infection rates of P. falciparum increased by 1.46 folds in HT, 1.28 folds in LT, and 1.15 folds in NT lines, respectively, compared to the control line. Paracentric inversions were observed on 2 locations on the 3L chromosomal arm of the NT line. Furthermore, the predictive linear model suggested faster adaptation of LT than HT and NT lines. Conclusion The present transgenerational laboratory-based study on An. stephensi provides novel insights into the effects of stressors on the life cycle, egg and wing size, vectorial competence, chromosomal inversions and adaptation. These findings aid in assessing malaria incidence trends and help in developing suitable intervention measures.